Features of application of court precedent in civil process of Ukraine - Vladykin, Oleksandr; Grachova, Oleksandra (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is devoted to the study of the peculiarities of the application of court precedent in the civil process of Ukraine. The general theoretical concept of judicial precedent is considered on the basis of legal doctrines of domestic and foreign scientists. The author’s interpretation of this lexical term and its main features is formed. The article contains an analysis of the definition of judicial precedent in the norms of legislation - the Civil Procedure Code of Ukraine. The importance of amending the legislation by supplementing the norm of Article 13 of the Law of Ukraine "On the Judicial System and the Status of Judges", Article 10 of the Civil Procedure Code of Ukraine, in which judicial precedent will be understood as a source of law, is emphasized. The authors of the article analyzed the use of court precedents in disputed court cases, cassation appeals. It has been studied that the positions indicated and published in the legal acts of the highest instance court in Ukraine—the Supreme Court—can be applied by the courts of the first and appellate instances. It was noted that it is important to adopt a separate article of the Civil Code of Ukraine, on the basis of which an algorithm will be developed for the Supreme Court to cancel the decisions of the courts of first instance and appeal due to the lack of previous practice of the Supreme Court in similar legal relations. Special emphasis was given to the analysis of the Supreme Court Decision in case № 711/17/19, which contains the arguments of the Supreme Court regarding the practical aspects of the annulment of the decisions of the lower court levels due to the lack of analysis and references to similar court cases formed earlier.